The opportunities and challenges of using mobile health in elderly self-care - Masoumeh Shahbazi; Hossein Bagherian; Mohammad Sattari; Sakineh Saghaeiannejad-Isfahani (Wolters Kluwer Medknow Publications, 2021)
Population aging is a phenomenon expanding around the world and will be increase the incidence of chronic diseases and health costs. This study was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA). A comprehensive literature search was performed on 4 databases (Web of Science, PubMed, Science Direct, and ProQuest) for English language studies from January 1, 2000, to December 31, 2019. The keywords used to extract relevant contents were "e-health," "Elderly care," "Self-care," "challenge," "Opportunity" etc., The search strategy led to a total of 638 potentially relevant papers, of which 19 papers met the inclusion criteria. The results showed that the challenges of using mobile health in elderly self-care can be divided into technical, human and managerial challenges. The resulting opportunities include reducing health care costs; no need to visit verbal and remote access to elderly information. The use of mobile health in the elderly has advantages and disadvantages. One of the advantages of that is improving physical activity and reducing care costs, but it may break the privacy. The disadvantages of that can be resolved by educating the elder men.